Re‐racialization of Addiction and the Redistribution of Blame in the White Opioid Epidemic. (28th May 2018) - Mendoza, Sonia; Rivera, Allyssa Stephanie; Hansen, Helena Bjerring
Abstract: New York City has the largest number of opioid dependent people of U.S. cities, and within New York, Whites have the highest rate of prescription opioid and heroin overdose deaths. The rise of opioid abuse among Whites has resulted in popular narratives of victimization by prescribers, framing of addiction as a biological disease, and the promise of pharmaceutical treatments that differ from the criminalizing narratives that have historically described urban Latino and black narcotic use. Through an analysis of popular media press and interviews with opioid prescribers and community pharmacists in Staten Island—the epicenter of opioid overdose in New York City and the most suburban and white of its boroughs—we found that narratives of white opioid users disrupted notions of the addict as "other, " producing alternative logics of blame that focus on prescribers and the encroachment of dealers from outside of white neighborhoods.